2007
DOI: 10.1159/000111767
|View full text |Cite
|
Sign up to set email alerts
|

Small Supernumerary Marker Chromosomes (sSMC) in Patients with a 45,X/46,X,+mar Karyotype – 17 New Cases and a Review of the Literature

Abstract: Small supernumerary marker chromosomes (sSMC) can appear in a numerically normal ‘basic karyotype’, but also in a numerically abnormal one like a Turner syndrome karyotype (= sSMCT). Here we present 17 new cases with such a mos 45,X/46,X,+mar karyotype. Moreover we reviewed all 512 cytogenetically similar cases available from the literature and supply for the first time data on occurrence, shapes and subgroups of this rare cytogenetic entity. sSMCT are very rare in the common population (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
2
28
0
6
Order By: Relevance
“…Since the idic(Y)(q11.23) cell line is more common and monocentric Y chromosomes are reported to be more stable than dicentric ones (Haaf and Schmid, 1990), 'initial' chromosome aberration is probably idic(Y)(q11.23), whereas i(Y)(p10) seems to be produced through the rearrangement of idic(Y)(q11.23). Taking into account previous reports (Haaf and Schmid, 1990;Stankiewicz et al, 2001;Codina-Pascual et al, 2004;DesGroseilliers et al, 2006;Liehr et al, 2007), one can suggest that instability of idic(Y)(q11.23) is the main reason for its loss and gain. Together this is evidence for post-zygotic origin of all cell lines apart from idic(Y)(q11.23) and suggests that the index case represents an example of dynamic mosaicism.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Since the idic(Y)(q11.23) cell line is more common and monocentric Y chromosomes are reported to be more stable than dicentric ones (Haaf and Schmid, 1990), 'initial' chromosome aberration is probably idic(Y)(q11.23), whereas i(Y)(p10) seems to be produced through the rearrangement of idic(Y)(q11.23). Taking into account previous reports (Haaf and Schmid, 1990;Stankiewicz et al, 2001;Codina-Pascual et al, 2004;DesGroseilliers et al, 2006;Liehr et al, 2007), one can suggest that instability of idic(Y)(q11.23) is the main reason for its loss and gain. Together this is evidence for post-zygotic origin of all cell lines apart from idic(Y)(q11.23) and suggests that the index case represents an example of dynamic mosaicism.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, Liehr et al (2007) have shown that the majority of cases of marker chromosomes derived from the Y chromosome are 45,X/46,X,der(Y) mosaics. It has been long suggested that mosaicism is produced by post-zygotic instability of rearranged Y chromosomes, especially in cases of dicentric chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these sSMC are derived from sex chromosomes, generally either sSMC(X) ring or sSMC(Y), inverted duplication/isodicentric chromosomes. 29 However, their exact chromosome break points are rarely defined. Future more precise characterization of sSMC(X) or sSMC(Y) using molecular cytogenetic techniques may provide greater understanding of their cause and effect.…”
Section: Advances In Genetic and Genomic Technologies For Clinical DImentioning
confidence: 99%
“…This concurs with the observations of the patient presented here with the absence of ovaries detected by the USG examination. Cole et al [1994] and Liehr et al [2007] reported MR for these Turner syndrome variant patients. Badeschi and colleagues [2008] described a male with severe MR with duplication on the X chromosome Xq12 to Xq12.1, which contains the OPHN1 gene.…”
Section: Discussionmentioning
confidence: 92%